Czynniki strategicznego sukcesu instytucji edukacyjnej MBA w Polsce : Identyfikacja i ocena empiryczna - Nogalski, Bogdan; Butkiewicz, Grzegorz (The Key Success Factors in Strategic Success of MBA Educational Institutions in Poland : Identification and Empirical Evaluation, 2008)
The elaboration concentrates on the identification and evaluation - based on empirical analysis-of behaviour patterns which allowed MBA educational institutions to achieve sustainable competitive advantage. The authors describe a model which should present a theoretical basis for process development necessary to obtain strategic market success. The article elaborates that there is a necessity of environment monitoring and it also suggests that strategic success of an MBA educational institution in Poland can be obtained when the competitive advantage is built on: unique competences, strong reputation and quality and wide variety of carefully chosen programmes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 256-266